Evaluating selfish spermatogonial selection and its role in human disease - Ralph, H (2018)
The majority of de novo mutations originate in the paternal germline. Prior evidence has shown that a subset of activating mutations arise spontaneously within the spermatogonial stem cell (SSC) and can expand clonally along the length of a seminiferous tubule. This process, Selfish Spermatogonial Selection (SSS), explains the high birth prevalence, and increase in frequency with paternal age, of several rare congenital disorders (e.g. Apert syndrome, achondroplasia). Quantification of these low-level mutations represents a significant technical challenge. Mutation-specific assays have been developed to assess mutation levels directly in sperm and testis samples; to date, however, only 16 loci in six genes, all of which encode members of the RAS-Mitogen-Activated Protein Kinase (RAS-MAPK) pathway, have been assessed. The aim of this thesis is to evaluate whether other mutations, genes and pathways are subject to SSS by developing scalable screening methods that allow distinction of true variation from confounding errors. My initial work focused on an existing discovery screen which utilised massively parallel droplet PCR combined with ultra-deep sequencing to assess a candidate gene panel. I undertook manual curation and targeted high-fidelity PCR to resolve a long-list of candidate variants. The validated variants display a striking overlap with clinically relevant mutations and double the number of SSS implicated genes in the RAS-MAPK pathway. Distinguishing signal from noise remains a significant challenge with PCR- based methods. To improve sensitivity, two different capture-based tech- nologies incorporating unique molecular identifiers (UMIs) were investigated. Target panels were developed to assess hotspots in candidate genes, including genes involved in cancer, intellectual disability and clonal haematopoiesis. The first mutations potentially subject to SSS outside the RAS-MAPK path- way is described, with the identification of mutations at hotspots in SMAD4, a key mediator of the TGF-β BMP signalling pathway. In summary, my work has strengthened the association of the RAS-MAPK pathway with SSS. Using refined methods to increase sensitivity and scalability, I also report the first hints that SSS may impact additional signalling processes in the testis.